The Influence of Auditors Professional Skepticism, Responsibility, and Independence on Audit Quality In Public Auditors in West Java - Asyari; Heni Suryanti; Padri Achyarsyah; Andi Pallawagau (CV ODIS, 2026)
The research aims to determine and analyze the influence of professional skepticism on audit quality, independence on audit quality, and accountability on audit quality. This research was conducted on auditors who work at Public Accounting Firms (KAP) in the West Java region. The research population was 160 KAP. And sampling was carried out randomly with a total of 40 KAPs. The research methodology was quantitative descriptive by distributing questionnaires. Data processing uses the SPSS 21 application. Data measurement is carried out through validity and reliability testing, normality tests, and autocorrelation tests. Hypothesis testing is carried out using multiple linear regression. The research results show that independence has a significant positive effect on audit quality. Responsibility or accountability has a significant positive effect on audit quality. And professional skepticism has a significant positive effect on audit quality. The R-square determination test shows that the three research variables are able to contribute to influencing audit quality, 75.3 percent of which is influenced by other factors.